Atomic level distributed strain within graphene divacancies from bond rotations. - Chen, Q; Robertson, A; He, K; Gong, C; Yoon, E; Lee, G; Warner, J (American Chemical Society, 2015)
Vacancy defects play an important role in influencing the properties of graphene and understanding their detailed atomic structure is crucial for developing accurate models to predict their impact. Divacancies (DVs) are one of the most common defects in graphene and can take three structural different forms through various sequences of bond rotations to minimize the energy. Using aberration-corrected transmission electron microscopy with monochromation of the electron source, we resolve the position of C atoms in graphene and measure the C-C bond lengths within the three DVs, enabling a map of bond strain to be generated. We show that bond rotations reduce the maximum single bond strain reached within a DV and help distribute the strain over a larger number of bonds to minimize the peak magnitude.